The modified multi-step thermal annealing process for highly efficient MAPbI3-based perovskite solar cells. (1st November 2018) - Jiang, Yaxiao; Pan, Lin; Wei, Dong; Li, Wenbiao; Li, Shaohua; Yang, Shi-E; Shi, Zhifeng; Guo, Haizhong; Xia, Tianyu; Zang, Jinhao; Chen, Yongsheng
Graphical abstract: Highlights: A modified multi-step (MMS) thermal annealing method is introduced in the fabrication process of MAPbI3 film. The decomposition of CH3 NH3 PbI3 films is effectively suppressed with MMS process. A maximum PCE of 14.7% for the device treated by MMS method is obtained at 180 °C. Abstract: Since the first report in 2009, the certified power conversion efficiency (PCE) of organic-inorganic halide perovskite solar cells (PSCs) has rapidly risen to 23.3%, which successfully demonstrates the importance of film morphology and quality management, especially for the planar heterojunction architecture based on solution-processed method. In this paper, the morphology, structure, optical and electrical properties of perovskite films treated by two different multi-step thermal annealing methods have been studied and compared. For the conventional multi-step (CMS) annealing method, the surface morphologies and optical properties of films are significantly influenced by the annealing temperature due to the decomposition of CH3 NH3 PbI3 . When the modified multi-step (MMS) method is adopted, the decomposition of CH3 NH3 PbI3 can be effectively suppressed. The best device treated by MMS method at 180 °C showed a short circuit current density of 20.85 mA/cm 2, an open circuit voltage of 0.96 V, a fill factor of 72.7%, and a PCE of 14.7%, which is a 23.5% enhancement in PCE relative to the maximum 11.9% treated by CMS method at 160 °C. These findings suggest that the efficiency of PSCs can be further improved by optimizing the preparation process.